Family History of Diabetes Is Associated With Delayed Fetal Postprandial Brain Activity - Schleger, Franziska; Linder, Katarzyna; Walter, Laura; Heni, Martin; Brändle, Johanna; Brucker, Sara; Pauluschke-Fröhlich, Jan; Weiss, Magdalene; Häring, Hans-Ulrich; Preissl, Hubert; Fritsche, Andreas (Frontiers in Endocrinology, 2018)
Introduction. We have previously shown that fetuses of mothers with gestational diabetes mellitus (GDM) and insulin resistance exhibit a prolongation of fetal auditory event-related brain responses (fAER) compared to fetuses of normal glucose tolerant women during an oral glucose tolerance test (oGTT). This implies that maternal metabolism may program the developing fetal brain. We now asked whether a family history of type 2 diabetes without metabolic programing also impacts fetal brain activity. We therefore investigated brain activity in fetuses of normal glucose tolerant mothers with and without family history of type 2 diabetes (FHD+ and FHD-). Methods. A 75g oGTT was performed in healthy pregnant women. Plasma glucose and insulin levels were measured after 0, 60 and 120 minutes. Each blood draw was preceded by magnetoencephalographic recordings of fAER. From a group of 167 participants, a sub-sample of 52 metabolically healthy women, 37 with a negative and 15 with a positive FHD (at least one first- or second-degree relative) was carefully selected based on the following inclusion criteria: inconspicuous pregnancy, no GDM, BMI 18.5-30 kg/m², no preterm birth and at least two fMEG with detectable fetal responses during oGTT. Results. An ANOVA showed a significant interaction between fMEG measurement time during the OGTT and FHD on fAER latency (F(2) =4.163, p=0.018). Fetuses of mothers with FHD+ had a prolonged fAER (273±113ms) compared to fetuses of mothers with FHD- (219±69ms) at 60 minutes during the oGTT (F(1)=4.902, p=0.032). There were no significant differences in age, BMI before pregnancy, weight gain during pregnancy and gestational age between the groups. Maternal glucose levels and insulin sensitivity were also not significantly different. Discussion. In addition to the previously shown influence of maternal metabolism on fetal brain activity, maternal family history of diabetes is also linked to fetal postprandial brain activity. This indicates that genetic and/or epigenetic factors modulate the postprandial brain response of the developing fetus.